Prognosis of patients with colonic carcinoma before, during and after implementation of complete mesocolic excision - Merkel, Susanne; Weber, K.; Matzel, Klaus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner (British Journal of Surgery, 2016)
The implementation of complete mesocolic excision (CME) for colonic cancer was accompanied by other important changes, including more patients with early diagnosis by screening and the introduction of adjuvant chemotherapy in patients with stage III disease. The contribution of CME remains unclear.In this observational study, data from patients with stage I-III colonic carcinoma were analysed by comparing five time intervals: 1978-1984 (pre-CME), 1985-1994 (CME development), 1995-2002 (CME implementation), 2003-2009 (CME) and 2010-2014 (CME), with a special focus on indicators of process and outcome quality.During the observed periods, the median age of patients increased (from 65 to 67 years), there were more right-sided carcinomas (from 17·0 to 32·4 per cent), more stage I disease (from 14·0 to 27·7 per cent) and fewer patients with regional lymph node metastases (from 42·7 to 32·0 per cent). The proportion of patients with pN0 disease and at least 12 examined regional lymph nodes increased (from 84·8 to 100 per cent) as did the R0 resection rate (from 97·0 to 100 per cent). Overall morbidity increased, whereas the in-hospital mortality rate was stable (range 1·8-3·7 per cent). Use of adjuvant chemotherapy in stage III colonic carcinoma increased from 0 to 79 per cent. The improvement in outcome quality was more evident in stage III than in stage I-II tumours. In stage III, the 5-year locoregional recurrence rate decreased from 14·8 to 4·1 per cent (P = 0·046) and the 5-year cancer-related survival rate increased from 61·7 to 80·9 per cent (P = 0·010).With CME, the quality indicators of process and outcome quality improved, especially in stage III colonic carcinoma. Adjuvant chemotherapy in stage III and multidisciplinary approaches in patients with metachronous distant metastases contributed to further outcome improvement.
EVALuna2:6780